27.4k views
5 votes
Help me please ! ASAP . . . .

Help me please ! ASAP . . . .-example-1
User Thang
by
5.4k points

1 Answer

4 votes


\textbf{Answer:}


\medskip\\ewline{\int\limits_(0)^(\infty){\bigl((1)/(y^2+1)\bigr)tan^(-1)(x)\mid_(x=0)^(x=\infty)}dy=(\pi^2)/(4)}


\medskip\\ewline\textbf{Step-by-step explanation:}


\medskip\\ewline\text{It's been a very long time since I've seen a calculus question.}\\ewline{\text{It might be because I haven't visited this site in a while.}}
\text{Anyway, on to the answer.}


\medskip\\ewline\text{When doing 2 integrals, work inside to out and treat the variables}\\ewline\text{ that aren't the ones being integrated as constants and proceed like normal.}
\medskip\medskip\\ewline\int\limits_(0)^(\infty){\int\limits_(0)^(\infty){(1)/((x^2+1)(y^2+1))}dx}dy


\\ewline{\text{Work inner to outer. Therefore, treat all y's as constants for now.}}
\\ewline{\text{By the integration formula: }\int(1)/(x^2+a^2)dx=(1)/(a)tan^(-1)((x)/(a))+C}


\\ewline{\int\limits_(0)^(\infty){\int\limits_(0)^(\infty){(1)/((x^2+1)(y^2+1))}dx}dy=}


\\ewline{\int\limits_(0)^(\infty){\bigl((1)/(y^2+1)\bigr)tan^(-1)(x)\mid\limits_(x=0)^(x=\infty)}dy=}


\\ewline{\int\limits_(0)^(\infty){\bigl((1)/(y^2+1)\bigr)(tan^(-1)(\infty)-tan^(-1)(0))}dy=}


\\ewline{\int\limits_(0)^(\infty){\bigl((1)/(y^2+1)\bigr)((\pi)/(2)-0)}dy=}


\\ewline{\int\limits_(0)^(\infty){\bigl((1)/(y^2+1)\bigr)((\pi)/(2))}dy}


\medskip\\ewline\text{Using the same integration formula as before.}


\medskip\\ewline{\int\limits_(0)^(\infty){\bigl((1)/(y^2+1)\bigr)((\pi)/(2))}dy=}


\\ewline{((\pi)/(2))tan^(-1)(y)\mid\limits_(y=0)^(y=\infty)=}


\\ewline{((\pi)/(2))(tan^(-1)(\infty)-tan^(-1)(0))=}


\\ewline{((\pi)/(2))((\pi)/(2)-0)=}


\\ewline{((\pi)/(2))((\pi)/(2))=}


\\ewline{(\pi^2)/(4)}


\bigskip\\ewline{\text{Therefore, the answer is }(\pi^2)/(4)}

User Ardal
by
5.4k points